Pemberdayaan Kader Terhadap Penigkatan Cakupan Asi Eksklusif Melalui Pijat Oksitosin pada Ibu Post Partum di Kabupaten Enrekang - Nur Laela; St. Nurbaya; Asma Sukarta; Nurjanna Nurjanna; Roni Roni (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The Community Service Program partners with the City Health Center of Enrekang Regency, South Sulawesi Province. The location of this PKM is in Kaluppini Village, Enrekang District, Enrekang Regency which is the working area of ​​the Enrekang Regency City Health Center. Oxytocin massage is a relaxation therapy that stimulates the central nervous system in the posterior and anterior pituitary which is carried out to help postpartum mothers to increase breast milk production. The results in this activity are 1. Increased knowledge and skills of Cadres on oxytocin massage, 2 Knowing the achievements of Posyandu Cadre assistance to assisted families who have babies as an evaluation material for increasing Exclusive Breastfeeding Coverage, and 3. Mothers and families will pay more attention to exclusive breastfeeding as an effort increased coverage of exclusive breastfeeding. Conclusion From the results of community service activities, there was an increase in the knowledge and skills of posyandu cadres to participate in the success of exclusive breastfeeding for infants As one of the government programs.